Bantuan Luar Negeri sebagai Bentuk Implementasi Economic Persuasion Amerika Serikat ke Sudan - Sindy Yulia Putri (Universitas Potensi Utama, 2022)
The foreign aid provided by the United States in the Darfur’s conflict, Sudan has received attentions from the global community. This assistance reflected on the policy of economic persuasion as a number of the United States’ political and economic interests in Sudan. The US was assumed to be inconsistent. The US still committed to provide aids to Sudan whereas it imposed economic sanctions on Sudan. A wide variety of aids included humanitarian assistance, food, sanitation, technical assistance, conditional loans, grants, and so forth. This paper has used a descriptive qualitative approach, because this study only described the US interests behind a number of foreign aid’s distributions, when the US carried out economic sanctions against Sudan. The result of this study is that the US empowered foreign aid as a form of realization of economic persuasion, especially a structural economic linkage. Although the US enforced economic sanctions on Sudan, the US still distributed foreign aid to that country. The US had ambitions to obtain an access to energies such as oil and gas, as well as to maintain a political stability in the African region. The US played a role in minimizing the Darfur’s conflict by providing a range of foreign assistances not only to normalize diplomatic relations with Sudan, but also to maintain sustainable partnerships with among countries in an African region.